Psychoactive Substance and Psychopathological Symptoms among Nigerian Secondary Schools Adolescents - Akpunne, Bede (International Neuropsychiatric Disease Journal, 2019)
Aim: Abuse of psychoactive substances among secondary school adolescents is a huge problem globally. This study examined the influence of psychoactive substance use on psychopathological symptoms among secondary school adolescents in Ede, Osun State, Southwestern Nigeria. Study Design: Cross-sectional survey design. Place of Study: Redeemer’s University Ede Osun state, Southwestern Nigeria. Methodology: Four hundred and ninety-six (496) secondary school adolescents (mean age 15.7 years) were purposively selected from five secondary schools in Ede metropolis. Substance Abuse Inventory (SABI) and Awaritefe Psychological Index (API Form-X) were used for data collection. Descriptive and inferential statistics were used for data analysis. Four hypotheses were tested using a Regression Analysis, Pearson Product Moment Correlation and Independent Sample t-test and at 0.05% level of significance. Results: A high prevalence of psychopathological symptoms was observed among the participants. Psychoactive substance use was observed to jointly and significantly predict psychopathological symptoms (R² = .106, p = .001). Sex has significant influence on manifested psychopathological symptoms with female adolescents reporting higher mean scores on insomnia, intellect disorder, heat disorder, mood disorder, alimentary track disorder and general psychopathology. Age was observed to be inversely correlated with psychopathological symptoms. Significant difference was found between drug users and non-user on severities of psychopathological symptoms. Conclusions: This research finding indicates a high prevalence of psychopathological symptoms; that the use psychoactive substance is significantly linked the psychopathological symptoms and that age of involvement in psychoactive substance is also a significant risk factor for psychopathology among adolescents.
Keywords: Psychoactive substance; Psychopathology; Adolescents; Nigeria